2020
DOI: 10.1007/s42729-020-00336-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biochar on Release Kinetics of Pb (II) and Zn (II) in a Calcareous Soil Polluted with Mining Activities

Abstract: Release kinetics governs the detachment and migration of potentially toxic trace elements (PTEs) over time between the solid phase and soil solutions. The assessment of PTEs' release behavior through time supports more accurate prediction models of toxicity in highly polluted soils. Recently, biochar, a charcoal black carbon ameliorant, was extensively applied for decreasing the release of Zn and Pb to the soil solution. This study was arranged during a short-term (45 days) incubation experiment to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…This similar method tried to solve the soil problem by reusing the existing waste materials, but the internal mechanism of the effect has not been explored in depth 33 , 34 . Some scholars attempted to introduce first principles in physics to solve the problem of soil heavy-metal pollution 35 , 36 . Balan et al analyzed the release kinetics of lead from soil, and Zhang et al analyzed the adsorption of kaolinite on Mg, Sb, Cu, As, Al, and other heavy-metal elements 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…This similar method tried to solve the soil problem by reusing the existing waste materials, but the internal mechanism of the effect has not been explored in depth 33 , 34 . Some scholars attempted to introduce first principles in physics to solve the problem of soil heavy-metal pollution 35 , 36 . Balan et al analyzed the release kinetics of lead from soil, and Zhang et al analyzed the adsorption of kaolinite on Mg, Sb, Cu, As, Al, and other heavy-metal elements 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…−1 ); AZ 0%, AZ 3%, and AZ 6%, Azolla at rates of (0, 3, and 6%). Means denoted by the same letter indicate no significant difference according to Duncan's tests at p < 0.05 However, the conjunction use of BC and AZ resulted in a significant increase in yield and quality via improvement soil properties, increasing soil organic matter which leads to soil carbon-rich that enhances soil microorganisms and nutrient availability resulting higher plant yield and its quality (Eissa 2019;Ghadimi et al 2021;Kabiri et al 2021). Also, combined application of biochar and Azolla improved the growth features of rosemary plants in calcareous soils of arid and semiarid regions (Sadegh Kasmaei et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The application of biochar and compost caused remarkable increases in the yield and quality of several field and vegetable crops through increasing the soil organic matter, nutrients availability and plant uptake 30 , 32 , 36 , 37 . The results of the current study revealed that there were increases in the soil microbial biomass carbon and nitrogen associated with the application of biochar and compost.…”
Section: Discussionmentioning
confidence: 99%